Modifikasi Syariah Pada Kerangka Risiko Return - Ega Anjani (STAI La Tansa Mashiro, 2024)
Sharia modifications in the risk and return framework are used to manage risk and achieve the desired level of return. This method involves using financial instruments that comply with Sharia principles and a thorough risk analysis to discover and manage the associated risks. Sharia insurance companies use Sharia modifications to manage their investment portfolios. In other words, they avoid financial instruments that are considered haram, such as riba (interest), maysir (gambling), and gharar (excessive uncertainty). Instead, they invest policyholder premium funds in financial instruments that comply with sharia principles, such as shares, bonds, and property. In addition, sharia modifications require a thorough risk analysis. Takaful insurance companies must understand and manage their investment risks. It includes risk identification, risk assessment, risk measurement and risk control. For sharia insurance, the risks that must be addressed include underwriting, investment, liquidity, and operational risks. Sharia modification aims to balance risk and return following Sharia principles in the risk and return framework. Takaful insurance companies seek to protect their policyholders financially while ensuring their investments align with the Sharia values they hold dear. In this situation, changing sharia in the context of risk and return is a comprehensive and comprehensive approach to managing sharia insurance. They can achieve their goal of providing financial protection per highly upheld Sharia values by combining Sharia principles, careful risk analysis and wise investment management